Land Perspectives: People, Tenure, Planning, Tools, Space, and Health - Chigbu, Uchendu Eugene; Chen, Ruishan; Ye, Chao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Good land administration and spatial enablement help to improve people's living conditions in urban, peri-urban, and rural areas. They protect people's land rights (including of individuals, communities, and the state) through good governance principles and practices. This makes research concerning land administration practices and geographic (spatial) sciences-whether in developed or developing countries-essential to developing tools or methods for securing natural resource rights for people. In the time of COVID-19, understanding the land and health or wellbeing nexus is also crucial for adequate living conditions for people in living urban, peri-urban, and rural areas. This Special Issue comprises 15 articles (including the editorial) that present insights on theories and practices on land administration and geographic (spatial) sciences in the context of land/water/forest-people-health-wellbeing nexus.